2002
DOI: 10.1210/en.2002-220534
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Glucocorticoid Treatment Programs Alterations in the Renin-Angiotensin System of the Ovine Fetal Kidney

Abstract: Ovine fetuses exposed to high concentrations of synthetic (dexamethasone, D) or naturally occurring glucocorticoids (cortisol, F) in utero during early gestation develop high blood pressure in adulthood. To investigate potential mechanisms involved, we examined the role of the renal renin-angiotensin system (RAS). Ewes were infused with isotonic saline (S, n = 11), D (n = 12, 0.48 mg/h), or F (n = 5, 5 mg/h) for 48 h between d 26 and 28 of gestation (term = 150 d). Ewes carrying twins (S, n = 5; D, n = 6; F, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
105
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(111 citation statements)
references
References 44 publications
6
105
0
Order By: Relevance
“…Despite that the intrarenal RAS is suppressed in the neonatal period in prenatally programmed hypertension in the rat, AT1R expression increases above control levels during the prehypertensive stage (97,114), without feedback suppression in kidney angiotensin I or II contents (97). In sheep that have been programmed to become hypertensive by maternal glucocorticoid treatment (115) or by maternal food restriction (70), upregulation of renal AT1R has been documented already in late gestation and at birth, respectively, perhaps reflecting the much more advanced maturation state of the ovine kidney. These findings are consistent with activation of RAS via upregulated AT1R and offer a potential role for the intrarenal RAS in the pathogenesis of prenatally programmed hypertension.…”
Section: Targets Of Programming In the Fetusmentioning
confidence: 99%
“…Despite that the intrarenal RAS is suppressed in the neonatal period in prenatally programmed hypertension in the rat, AT1R expression increases above control levels during the prehypertensive stage (97,114), without feedback suppression in kidney angiotensin I or II contents (97). In sheep that have been programmed to become hypertensive by maternal glucocorticoid treatment (115) or by maternal food restriction (70), upregulation of renal AT1R has been documented already in late gestation and at birth, respectively, perhaps reflecting the much more advanced maturation state of the ovine kidney. These findings are consistent with activation of RAS via upregulated AT1R and offer a potential role for the intrarenal RAS in the pathogenesis of prenatally programmed hypertension.…”
Section: Targets Of Programming In the Fetusmentioning
confidence: 99%
“…Thus it appears that in the sheep, as well as in the rat, the dose of dexamethasone required to program offspring hypertension is greater than the minimum dose that can impair maternal and/or fetal weight gains. Interestingly, a considerably larger dose of dexamethasone (ϳ240 g⅐kg Ϫ1 ⅐day Ϫ1 ) infused into pregnant sheep on days 26 and 27 of gestation did not significantly alter the weights of fetuses at 130 days gestation (27). Using a similar dose regimen, Dodic et al (10) showed that birth weight was not significantly different and reported that weights at 100, 300, and 560 days of postnatal age were "similar" to controls (data not given).…”
mentioning
confidence: 92%
“…We found that baseline GFR adjusted for body weight was significantly decreased in male but not female adult sheep prenatally exposed to clinically relevant doses of betamethasone. Findings from a number of studies have demonstrated lower nephron endowment, high blood pressure, and altered ANG receptor expression in glucocorticoid-exposed models of fetal programming (11,33,54,55). To date, few studies have assessed whether these changes result in impaired or altered renal function, especially in adult offspring.…”
mentioning
confidence: 99%